Hydrodynamic assessment of planing hulls using overset grids. (April 2017) - Sukas, Omer Faruk; Kinaci, Omer Kemal; Cakici, Ferdi; Gokce, Metin Kemal
Highlights: Overset grid results are in better accordance with experiments in high Fr while using rigid body motion is better in low Fr . Savitsky approach implementing Schoenherr's formula returns high frictional resistance in the whole Fr number range. The method also generates very high pressure resistance at low Fr numbers where the hull is in the displacement mode. If the resistance components of a planing hull are to be evaluated, it would be misleading to rely on Savitsky's approach. The squat flow regime of the hull is numerically visualized. Low pressure region in the flow moves back with increasing Fr . Abstract: In conjunction with high performance computers, recent developments in computational science paved the path to more accurate representation of body motions inside fluids. Small motions inside the flow can be computationally approximated by using rigid body motion but it is incapable of accurately predicting the large motions of a planing vessel. The implementation of overset grid has made it possible to better approximate the complex fluid-structure interaction problem of the planing regime. The focus of this study was to evaluate the opportunity of using an overset grid system to numerically solve the flow around a planing hull and to understand the planing regime with this invaluable tool. It was shown in this study that the overset grid better captures the large motions of the planing hull at high Froude numbers. Then, the results obtained by overset grid were used to calculate the resistance components of a planing hull in a wide Froude number range. The resistance components were discussed with respect to values generated by Savitsky approach. Using the benefits that the computational science brings, the flow was visualized to explain some underlying physics relevant to the planing regime.